MENINGKATKAN KOMPETENSI LITERASI DIGITAL BERBASIS DIGITAL LITERACY GLOBAL FRAMEWORK (DLGF) DI GLOBAL PERSADA MANDIRI BEKASI - Adi Muhajirin; Ajif Yunizar Pratama Yusuf (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Digital literacy is the ability to search, understand and use information from various digital sources wisely. UNESCO has created a framework for measuring digital literacy levels called the Digital Literacy Global Framework (DLGF). That DLGF has instruments consisting of 1) Information and data literacy, 2) Communication and collaboration, 3) Digital Content Creation, 4) Safety, 5) Problem Solving and transformed by KOMINFO into 4 pillars of literacy to support digital transformation, namely 1) Digital Skills, 2) Digital Ethics, 3) Digital Safety and 4) Digital Culture. The purpose of this community service is to measure and improve the digital literacy skills of the Bekasi City community in dealing with hoax news and to analyze the extent of digital literacy competence through the DLGF framework. Where as many as 234,444 participants took part in the activities carried out by cybercreating in the city of Bekasi with a total of 2,564,941 and only about 9% of the population had just participated. for the method used is descriptive method with a quantitative approach. The data collection technique is a questionnaire method and library research (Library Research). The results obtained are an increase in Digital Skill 5.47%, Digital Ethics 8.79%, Digital Safety 7.63%, and Digital Culture 8.47%).